The Process of Implementing the Discovery Learning Model Assisted by Diction in Instagram Posts to Enhance and Skills in Writing Poetry - Dinda Luciana; Wikanengsih (JLER (Journal of Language Education Research), 2026)
Researchers identified problems in learning to write poetry. The existence of teachers who still teach in a teacher-oriented style, the existence of students who still have difficulty in pouring ideas in writing poetry, the existence of students who still have difficulty in choosing the right diction, and the lack of interest of students in learning Indonesian, especially writing poetry are the sources of ideas in this study. Diction-assisted discovery learning on Instagram posts can be used as a tool to overcome some of these problems. This study aims to determine the process of applying the diction-assisted discovery learning learning model on Instagram posts in increasing students' interest and poetry writing skills during learning. The method used in this study is qualitative descriptive. The population taken in this study is grade VIII students of Cimindi Adventist Junior High School. In this study, the average result of the teacher's observation result was 92.35% and the student's observation result was 92.3%, which showed very good results.